Exploring behavioural branding, brand love and co-creation - Kaufmann, H. R. (2017)
Purpose: This paper aims to contribute to the understanding of the complex consumer brand relationships by holistically exploring the dynamics between brand love and co-creation, how they are impacted by behavioural branding and their combined impact to brand loyalty. Design/methodology/approach: This is a conceptual paper, based on extensive and thorough literature review on the fields of brand love, behavioural branding, brand communities and co-creation, that leads to the formulation of a proposed synthesized framework. Findings: The authors propose that consumers experiencing brand love are more willing to engage in an active co-creating behaviour in the context of a brand community, especially when brand representatives vividly communicate the brand values and motivate consumers to engage. This process is moderated by the product/service category and level of customer involvement with it, and it produces a combined positive impact on brand loyalty. Research limitations/implications: The proposed conceptual framework needs to be validated through empirical research. However, even at this initial stage, it may have a significant impact, especially as it highlights the role of brand representatives and how they could drastically moderate the relationship between the brand and the consumer. Originality/value: This is the first attempt to incorporate the constructs that are significant to the consumer–brand relationship research stream in one conceptual framework. The synthesis of these concepts will contribute to the improved understanding of the consumer–brand relationship, and its dynamics and will equip managers with a novel approach to the central role of behavioural branding.